2007
DOI: 10.1016/j.thromres.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Protease activation of calcium-independent phospholipase A2 leads to neutrophil recruitment to coronary artery endothelial cells

Abstract: Introduction-Thrombin or tryptase cleavage of protease-activated receptors (PAR) on human coronary artery endothelial cells (HCAEC) results in activation of a membrane-associated, calciumindependent phospholipase A 2 (iPLA 2 ) that selectively hydrolyzes plasmalogen phospholipids. Atherosclerotic plaque rupture results in a coronary ischemic event in which HCAEC in the ischemic area would be exposed to increased thrombin concentrations in addition to tryptase released by activated mast cells present in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…The classification of our target enzyme activity as intracellular is based on previous methodical investigations (Lasch et al, 2003) showing an almost complete (more than 90%) inhibitory effect of calcium ions on enzyme activity and a 70% inhibition of the enzyme activity by bromoenole lactone (BEL), a complete inhibitor of iPLA 2 (Jenkins et al, 2001;Lucas et al, 2005;Song et al, 2006;White and McHowat, 2007). As cPLA 2 has ubiquitary action with only micromolar calcium concentrations, it might also have contributed to the measured PLA 2 activity here.…”
Section: Analysis Of Pla 2 -Activitymentioning
confidence: 96%
“…The classification of our target enzyme activity as intracellular is based on previous methodical investigations (Lasch et al, 2003) showing an almost complete (more than 90%) inhibitory effect of calcium ions on enzyme activity and a 70% inhibition of the enzyme activity by bromoenole lactone (BEL), a complete inhibitor of iPLA 2 (Jenkins et al, 2001;Lucas et al, 2005;Song et al, 2006;White and McHowat, 2007). As cPLA 2 has ubiquitary action with only micromolar calcium concentrations, it might also have contributed to the measured PLA 2 activity here.…”
Section: Analysis Of Pla 2 -Activitymentioning
confidence: 96%
“…Most of the intracellular PLA 2 enzymes need calcium in micromolar concentrations at most (cPLA 2 ) or are completely independent of calcium (iPLA 2 ). The activity of enzymes obtained from the subjects in this study were almost completely (more than 90%) inhibited by calcium ions and strongly (70%) inhibited by bromoenole lactone (BEL), a total inhibitor of iPLA 2 (Jenkins et al 2001;Lucas et al 2005;Song et al 2006;White and McHowat 2007). In contrast, previous studies excluded the contribution of PAFhydrolases to the measured activity level, as PAF-hydrolases do not cleave the here used NBDC 6 -HPC ® substrate.…”
Section: Discussionmentioning
confidence: 59%
“…Leukocytes express a PAF receptor that enhances their endothelial cell adhesion and induces their β-integrin-mediated transmigration (Prescott et al, 2002). In previous studies, we have shown that thombin- or tryptase-stimulated endothelial cells demonstrate increased calcium-independent phospholipase A 2 activity, resulting in increased PAF production and PMN adherence (Kell et al, 2003; Vinson et al, 2005; McHowat et al, 2001; Rickard et al, 2005; Meyer et al, 2005; White and McHowat, 2007a; White et al, 2007b). We have shown that methyl arachidonyl fluorophosphonate (MAFP) inhibits PAF acetylhydrolase (PAF-AH) the enzyme responsible for PAF degradation, and increases PAF production and PMN adherence to endothelial cell monolayers (Kell et al, 2003; Vinson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%